3, 5-Diethyl-2r, 6c-di(4-chlorophenyl)piperidin-4-one picrate: synthesis, spectral, biological, DFT, ADME and molecular docking studies. (17th December 2022) - Savithiri, S.; Bharanidharan, S.; Rajarajan, G.; Sugumar, P.; Arockia Doss, M.
ABSTRACT: By using spectral methods, the 3, 5-diethyl-2r, 6c-di(4-chlorophenyl)piperidin-4-one picrate (DEDCPP) molecule was synthesised and characterised by FT-IR, NMR ( 1 H and 13 C), UV–Vis and Fluorescence spectral techniques. The molecular structure was optimised using the density functional theory (DFT) method with B3LYP/6-311++G(d, p) basis set. The dipole moment, polarisability and first-order hyperpolarisability demonstrate the good nonlinear optical (NLO) feature of the title molecule. Natural bonding orbital (NBO) analysis was used to determine the electron densities of donor (i) and acceptor (j) bonds as well as the hyperconjugative interaction energy (E (2) ). In highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) calculations, the smaller energy gap value was discovered. The Mulliken atomic charges of the carbon, nitrogen, chlorine and oxygen atoms were calculated at the same level of theory. The thermodynamic properties of the title compound were calculated at different temperatures in gas phase. The synthesised compound DEDCPP was screened for its antibacterial activity against Escherichia coli, Bacillus subtilis and Vibreo cholerae and antifungal activity against Candida albicans, Aspergillus niger and Trichophyton rubrum . The interaction of the title compound to bind to a target protein was studied using molecular docking analysis. GRAPHICAL ABSTRACT: UF0001